2014
DOI: 10.1124/jpet.114.216382
|View full text |Cite
|
Sign up to set email alerts
|

Clinically Relevant Doses of Candesartan Inhibit Growth of Prostate Tumor Xenografts In Vivo through Modulation of Tumor Angiogenesis

Abstract: Angiotensin II receptor type 1 blockers (ARBs), widely used antihypertensive drugs, have also been investigated for their anticancer effects. The effect of ARBs on prostate cancer in experimental models compared with meta-analysis data from clinical trials is conflicting. Whereas this discrepancy might be due to the use of supratherapeutic doses of ARBs in cellular and animal models as compared with the clinical doses used in human trials, further investigation of the effects of clinical doses of ARBs on prost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 35 publications
1
26
0
Order By: Relevance
“…The TUNEL assay for in situ detection of apoptosis was performed using the ApopTag® Fluorescein in Situ Apoptosis detection kit (Millipore, MA) as previously (Alhusban et al, 2014; Goc et al, 2012). Fixed frozen sections from prostate tumor xenografts were permeabilized in ethanol: acetic acid [2:1] mixture and labeled with fluorescein 12-dUTP using terminal deoxynucleotidyl transferase.…”
Section: Methodsmentioning
confidence: 99%
“…The TUNEL assay for in situ detection of apoptosis was performed using the ApopTag® Fluorescein in Situ Apoptosis detection kit (Millipore, MA) as previously (Alhusban et al, 2014; Goc et al, 2012). Fixed frozen sections from prostate tumor xenografts were permeabilized in ethanol: acetic acid [2:1] mixture and labeled with fluorescein 12-dUTP using terminal deoxynucleotidyl transferase.…”
Section: Methodsmentioning
confidence: 99%
“…AGTR1 acts as a novel component of the renin-angiotensin system (RAS) to affect the blood pressure and heart hypertrophy (15), targeting of renin-angiotensin system (RAS) through AGTR1 blocker is associated with the resistance phenomenon in treatment of resistant breast cancers. And now the AGTR1 blocker has been applied in the clinical oncology, such as the losartan for breast cancer (22) and candesartan for prostate cancer (23). And now emerging evidences showed that AGTR1 regulates the cell proliferation during cancer development, and promotes tumor invasion, migration, metastasis and angiogenesis (24).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the increased production of vascular endothelial growth factor (VEGF), which plays a critical role in tumor angiogenesis, is known to contribute to the growth and development of prostate cancer [16,17] . On the other hand, the angiogenesis induced by HT1080 cells is mainly dependent on the production of VEGF [18,19] , and HT1080 cells enhance the survival, migration, and Representative confocal laser micrographic images showing the distribution of PGP 9.5-ir nerve fibers (green) and α-SMA-ir neovessels (red) in the mouse cornea treated with systemic saline or NGF for 7 days immediately ( a , b1-3 ) after or from 7 days ( c , d1-3 ) after the implantation of a gel containing DU145 cells.…”
Section: Discussionmentioning
confidence: 99%